2009
DOI: 10.1002/ijc.24706
|View full text |Cite
|
Sign up to set email alerts
|

Association of HPV16 E6 variants with diagnostic severity in cervical cytology samples of 354 women in a US population

Abstract: It has been suggested that DNA sequence variants of HPV16 contribute to differences in the behavior of individual cervical lesions. To address this question, we have analyzed the association of HPV16 variants with diagnostic severity in 354 HPV16-positive Oklahoman women. HPV16 variant status was determined by PCR amplification and DNA sequencing of the E6 open reading frame. European sequences were identified in 86% of samples and 14% were non-European. Of the 51 nonEuropean cases, 61% were Asian-American, 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 41 publications
9
62
1
1
Order By: Relevance
“…In combination with the fact that HPV83m was isolated from an HSIL from a cervical smear, these results are strongly indicative of the oncogenic potential of this new variant, HPV83m. This idea is consistent with other studies that have reported the impact of E6 variants of HPV16 on the natural history of an infection (Asadurian et al, 2007;Da Costa et al, 2002;Grodzki et al, 2006;Richard et al, 2010;Wu et al, 2006;Zehbe et al, 1998;Zuna et al, 2009). In addition, we have demonstrated, by reverting the mutations in the second zinc-finger region of E6m, the importance of these mutations to this induction of host-cell proliferation; we show that cells expressing E6r-E7 of HPV83r exhibited the same proliferation as cells expressing E6-E7 of HPV6 and were not able to form colonies in soft agar cultures.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In combination with the fact that HPV83m was isolated from an HSIL from a cervical smear, these results are strongly indicative of the oncogenic potential of this new variant, HPV83m. This idea is consistent with other studies that have reported the impact of E6 variants of HPV16 on the natural history of an infection (Asadurian et al, 2007;Da Costa et al, 2002;Grodzki et al, 2006;Richard et al, 2010;Wu et al, 2006;Zehbe et al, 1998;Zuna et al, 2009). In addition, we have demonstrated, by reverting the mutations in the second zinc-finger region of E6m, the importance of these mutations to this induction of host-cell proliferation; we show that cells expressing E6r-E7 of HPV83r exhibited the same proliferation as cells expressing E6-E7 of HPV6 and were not able to form colonies in soft agar cultures.…”
Section: Discussionsupporting
confidence: 92%
“…These HPV16 variants seem to be risk factors for viral persistence; this is probably because of modification of the immunogenic properties of the virus (Grodzki et al, 2006). In fact, differential pathogenicity of HPV16 variants with mutations in E6 has been reported for cervical high-grade squamous intraepithelial lesions (HSIL), invasive cervical cancer and anal HSIL (Da Costa et al, 2002;Grodzki et al, 2006;Wu et al, 2006;Zehbe et al, 1998;Zuna et al, 2009 HPV16 induce markedly faster dividing when grown as organotypic raft cultures (Asadurian et al, 2007;Zehbe et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A study suggested that there appeared to be differences among the HPV16 variant categories in the risk for progression to cervical cancer, but all variant categories were associated with the development of cancer. 30 However, the mechanism of different variants to cause the development of cervical neoplasia remains unknown, although the carcinogenetic potential of HPV variants might be altered due to differences in the biological behavior of variant. In addition, the potential oncogenicity of variants might be dependent on host genetic differences between populations.…”
Section: Epidemiologymentioning
confidence: 99%
“…Factors favoring HPV persistence versus clearance are still poorly understood, but several studies have suggested that intratype genetic variations may influence persistence and clinical outcome (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). This phenomenon may be explained by natural variants that alter the immunogenic and/or carcinogenic properties of the virus.…”
Section: Introductionmentioning
confidence: 99%